2022
DOI: 10.3390/mi13030412
|View full text |Cite
|
Sign up to set email alerts
|

Long Stroke Design of Piezoelectric Walking Actuator for Wafer Probe Station

Abstract: In order to develop a high-resolution piezoelectric walking actuator with a long stroke for the wafer probe station, this work presents a design of a piezoelectric walking actuator with two auxiliary clamping feet elastically attached to major clamping feet. Its construction was introduced and its operating principle was analyzed. Structure design details were discussed and a prototype was proposed. The prototype was fabricated and tested. The experimental results show that the proposed actuator can operate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recent works have shown that fuzzy logic improves the performance of conventional controllers in the presence of disturbances and nonlinear behavior [14][15][16]. It has been found that the action of actuators can be reduced by up to 50% by running a fuzzy controller instead of a PID controller, thereby reducing energy consumption and associated costs [17,18]. Researchers have used fuzzy logic to identify system parameters and modify controller gains because its implementation is relatively simple.…”
Section: Related Workmentioning
confidence: 99%
“…Recent works have shown that fuzzy logic improves the performance of conventional controllers in the presence of disturbances and nonlinear behavior [14][15][16]. It has been found that the action of actuators can be reduced by up to 50% by running a fuzzy controller instead of a PID controller, thereby reducing energy consumption and associated costs [17,18]. Researchers have used fuzzy logic to identify system parameters and modify controller gains because its implementation is relatively simple.…”
Section: Related Workmentioning
confidence: 99%
“…As the extension of the piezoelectric elements is small; therefore, the inchworm device needs to be designed with a clamping unit to clamp the slide tightly and the drive should have a self-locking ability when the signal is removed. The recent works on the self-locking at rest feature of Inchworm drive include [37][38][39][40][41]. In most of these self-locking mechanisms, the piezo actuator itself moves and the guiding component remains stationary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it relies on friction to drive the actuator to achieve both large stroke and high precision motion. Currently, the piezoelectric motors reliant on friction can be divided into ultrasonic type [ 11 , 12 , 13 ], inertial type [ 14 , 15 , 16 ] and inchworm type [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%